A Hospital Based Study on Female Genital Tuberculosis in Central India - Swati Patel; P. L. Dhand (International Journal of Medical Research and Review, 2016)
Introduction: In developing countries like India tuberculosis (TB) is common and still a major cause of infertility. Female genital tuberculosis is one form of extra pulmonary TB. Genital TB may be asymptomatic and diagnosis requires a high index of suspicion. Early diagnosis may improve the outcome before permanent tissue damage get established. The objective of this study was to evaluate the prevelance and clinico-pathological aspects and diagnosis of female genital tuberculosis (FGTB).Method: A total of 21 cases of female genital tuberculosis were diagnosed from 1672 patients over a period of 2 years, studied from January 2013 to December 2015. The diagnostic procedure used were endometrial curettage and biopsy, histopathological examination, culture, stain for Acid fast bacilli in correlation with clinical presentation ,organ involvement, hysterosalpingography(HSG), Ultrasonography (USG)and laparoscopy. Most of the specimens received were endometrial curettage and biopsies.Result: Female genital TB accounted for 1.25% of all tuberculosis patients in this study. The highest incidence was between 21-30 years of ages, but the patient ranged from 18-60 years. FGTB involves the endometrium (16 ), fallopian tube (4),cervix (1). Out of all cases, 7 demonstrate typical epitheloid granuloma and rest with atypical tuberculous lesion, acid-fast bacilli in tissue section were detected in 3 cases of endometrium, 1 case of fallopian tube and culture positive in 3 cases of endometrium, 1 case of fallopian tube.Conclusion: Female genital tuberculosis is not uncommon in developing countries like India and indicates a strong relation between genital TB and infertility. The diagnosis of FGTB is challenging. Therefore, if possible genital TB is to be frequently diagnosed and considered in differential diagnosis of causes of infertility, in correlation with clinical and other diagnostic modalities.